The conceptual metaphor of ‘Life is a journey’ in Kazakh cognition - Beknazarova, Ulzhan; Saduakasuly, Zhenis; Suleimenova, Zharkynbike; Aman Abasilov, Kuldirsin Saryshova, (Opción, 2020)
The subject of research is the investigation of conceptual metaphors of LIFE in poetry. The study applies the principles of Conceptual Metaphor Theory (CMP), specifically the distinction between the source domain and the target domain. As a result, the knowledge of Kazakhs about the source domain is explicit and detailed as compared to life. In conclusion, the principles of CMP were found to be useful in organizing and explaining the consistent use of the ‘Life is a journey’ metaphor in Kazakh literature.